Elucidating fault-related fold mechanics: a 2D finite element analysis of bending, slip, and buckling mechanisms - Khalifeh-Soltani, Anis; Alavi, Seyed Ahmad; Ghassemi, Mohammad Reza; Ganjiani, Mehdi; Derakhshani, Reza (Frontiers in Earth Science, 2023)
Fault-related folds are present in most tectonic settings and may serve as structural traps for hydrocarbons. Due to their economic importance, many kinematic models present for them.Unfortunately, most of them have predominantly concentrated on the sliding mechanism parallel to the layering and often ignore the integral role of buckling in folding processes. This study is at the forefront of exploring the interplay among, sliding, buckling, and bending in the formation of the three fundamental types of fault-related folds: detachment, fault-propagation, and fault-bend folds. To this end, we developed five sets of two-dimensional (2D) finite element models, embodying both elastic and elastic-plastic behaviors. Our results indicate that sliding parallel to layering and faults, in conjunction with buckling, are the predominant mechanisms in fault-related folding. The strain ellipse patterns in our models are consistent with those observed in buckling models, thus affirming the significance of buckling in these geological structures. Furthermore, our models demonstrate that fault slip diminishes from the periphery towards the center in all three types of fault-related folds, in contrast to interlayer slip, which intensifies from the edge towards the center. In essence, a diminution in fault slip at the center is balanced by an augmentation in interlayer slip, leading to thickening and buckling. The genesis of all three fault-related fold types is attributed to the reduction in fault slip, with their distinctiveness defined by the location of this reduction: at the detachment fault tip for detachment folds, at the ramp tip for fault-propagation folds, and at the upper flat for fault-bend folds.